Interactive effects of high temperature and ozone on COPD deaths in Shanghai. (1st June 2022) - Fu, Shihua; Zhou, Yi; Peng, Li; Ye, Xiaofang; Yang, Dandan; Yang, Sixu; Zhou, Ji; Luo, Bin
Abstract: Heatwave occurs more frequently under climate change, induce increasing health burden globally. Aside from heatwave, the increase of global temperature is also accompanied by an increase in ozone concentration, indicating the necessity of exploring the potential interaction between ozone and temperature on the risk of health hazards. Therefore, we collected data of daily chronic obstructive pulmonary disease (COPD) deaths and ambient environmental data from 2008 to 2017 Pudong, Shanghai to explore the interactive effects of temperature and ozone on COPD deaths. We found that increasing temperature (>10 °C) was significantly associated with COPD deaths (relative risk [RR] 1.4669, 95% CI: 1.2485, 1.7234). With each 10μg/m3 ozone increase in summer, RR associated with COPD deaths was 1.0173 (95%CI: 1.0026, 1.0323). Bivariate polynomial model and GAM model, including interaction terms, showed that the effect of ozone on COPD deaths was significantly enhanced in heatwaves, with a RR of 1.0047 (95% CI: 1.0015, 1.0079). In conclusion, there is an interactive effect of ozone and heatwaves on COPD deaths, emphasizing the importance of controlling ozone pollution in heatwaves weathers. Graphical abstract: Image 1 Highlights: The temperature (>10 °C) was positively associated with COPD mortality risk, with greater mortality risk on exposure days. Ozone was significantly associated with an increased risk of COPD mortality in summer. This study evaluates the interaction of high temperature and ozone. Summer heat waves may increase ozone health effects.